2016
DOI: 10.1155/2016/1801658
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Ordering and Pricing Policies for Seasonal Products: Impacts of Demand Uncertainty and Capital Constraint

Abstract: With a stochastic price-dependent market demand, this paper investigates how demand uncertainty and capital constraint affect retailer's integrated ordering and pricing policies towards seasonal products. The retailer with capital constraint is normalized to be with zero capital endowment while it can be financed by an external bank. The problems are studied under a low and high demand uncertainty scenario, respectively. Results show that when demand uncertainty level is relatively low, the retailer faced with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Existing research on SCF mainly involves its definition [1,8,13], mode [2,7,14], and role [1,8]. Other extended research also include companies' adoption of SCF [15,16], as well as integrated financing and operating decisions of companies under the SCF framework [17,18].…”
Section: Research On Supply Chain Finance (Scf)mentioning
confidence: 99%
“…Existing research on SCF mainly involves its definition [1,8,13], mode [2,7,14], and role [1,8]. Other extended research also include companies' adoption of SCF [15,16], as well as integrated financing and operating decisions of companies under the SCF framework [17,18].…”
Section: Research On Supply Chain Finance (Scf)mentioning
confidence: 99%
“…Shi et al [37] studied the optimal order quantity and the optimal pricing problem of seasonal products under the conditions of market demand uncertainty and a capitalconstrained retailer. Shi et al [38] designed a simple intelligent purchasing decision support system for the capitalconstrained retailers to help them determine the integrated procurement time, quantity, and financing decisions for the seasonal products.…”
Section: The Retailer's Capital Constraintsmentioning
confidence: 99%
“…In the completed competitive banking market, research has shown that capital constraints do not influence retailer's optimal decision [8,9]. On the contrary, capital constraints affect a retailer's strategy by using its internal capital and interest rate when it secures a loan from a noncompetitive banking market [10] or faces uncertainty demand in a price-dependent market [11,12]. To avoid risks, banks always require a credit guarantee from the upstream manufacturer when they offer the SME retailer a loan.…”
Section: Interface Of Operations and Financing Decisionsmentioning
confidence: 99%